Acción del veneno de Bothrops jararacussu de Argentina sobre la coagulación sanguínea - Maruñak, S.L. (2006)
The envenomation by snakes of the genus Bothrops of Argentina causes local and systemic signs. Among the systemic damages, bothropic venoms induce a wide variety of effects on blood coagulation, haemorrhage, shock and renal failure. In this paper the effects of Bothrops jararacussu venom from Argentina on the hemostatic system were determined. In order to estimate blood-clotting, fibrinolytic and defibrinating activities of the venom, in vitro and in vivo tests were employed. The ability to degrade fibrinogen and the lethal dosis (DL50) also were determined. The B. jararacussu venom appears to be fibrinogenolytic and the values obtained for assayed activities were minimum blood-clotting concentration 18,5 ? g/ml, minimum fibrinolytic dose 9,5 mg/ml, minimum defibrinating dose 1,56 ?g, LD50 43,52 ?g/mouse. These results differ from those obtained for other species of genus Bothrops, or from the same species that inhabits in different South American regions. It is concluded that Bothrops jararacussu venom from Argentina largely affects blood coagulation system, and that the procoagulant and anticoagulant activities exhibited by this secretion may contribute to the lethality of the venom, since they could promote hemorrhages which could lead to renal failure and death of the victim in severe envenomation.